COVID‐19 pneumonia and pulmonary microembolism in a patient with B‐thalassemia major. Issue 12 (25th September 2020) - Marziali, Marco; Ribersani, Michela; Losardo, Anna Annunziata; Taglietti, Fabrizio; Pugliese, Pellegrina; Micozzi, Alessandra; Gentile, Giuseppe; Angeloni, Antonio
Abstract: We think that thalassemia is not necessarily a cause of aggravation of the clinical course in COVID‐19; however, certain key factors must be considered, such as the anemic condition, the likely pathogenic role of the virus on hemoglobin, and the hypercoagulable state to prevent any complications. Abstract : We think that thalassemia is not necessarily a cause of aggravation of the clinical course in COVID‐19; however, certain key factors must be considered, such as the anemic condition, the likely pathogenic role of the virus on hemoglobin, and the hypercoagulable state to prevent any complications.